Assessment Hormonal Disorders of Women in Oral and Vaginal Changes (Medico Legal Update, 2020)
Hormonal deficiencies may contribute to the development of abnormalities of oral and vaginal tissues, suchas pain, desquamation, recurrent oral, vaginal ulceration and delayed post-surgical healing .This study wasdone to determine the differences of cell activity in oral and vaginal mucosa .A total of 200 females of different age groups were used in this study Oral smears were obtained from thebuccal mucosa by scraping the area gently using a wooden tongue depressor while vaginal smears wereobtained from the proximal portion of the lateral wall of the vagina using Ayre’s spatula by scraping the areagently . In order to find to change in mucosa during different phases of menstrual cycle .In two groups the present results revealed that vaginal cytological patterns of each group is similar to theoral cytological pattern with some differences .In conclusion significant correlation between the hormonal fluctuations in woman and the degree ofmaturation of their oral epithelium was revealed in this study .